Post Stroke Seizures and Epilepsy: From Proteases to Maladaptive Plasticity - Altman, Keren; Shavit-Stein, Efrat; Maggio, Nicola (Frontiers in Cellular Neuroscience, 2019)
Post stroke epilepsy (PSE) is the most common cause of seizures in the elderly, yet its underlying mechanism is poorly understood. The classification of PSE is confusing, and there is neither a clear agreement on its incidence and prognosis nor a consensus about specific treatments. The diagnosis of PSE requires the occurrence of late seizures: epileptic events occurring one week or more after an ischemic stroke. Late seizures differ from early seizures by the presence of permanent structural changes in the brain. Those structural changes cause a shift in the regulation of neuronal firing and lead to circuit dysfunctions, and thus to a long-term epileptic condition. The coagulation cascade and some of its major components, serine proteases such as thrombin, are known to participate in the acute phase of a stroke. Recent discoveries found that thrombin and its protease-activated receptor 1 (PAR1), are involved in the development of maladaptive plasticity. Therefore, we suggest that thrombin and PAR1 may have a role in the development of PSE by inducing permanent structural changes after the ischemic events towards the development of epileptic focuses. We are confident that future studies will lead to a better understanding of the pathophysiology of PSE, as well as development of more directed therapies for its treatment.